2019
DOI: 10.1063/1.5124391
|View full text |Cite
|
Sign up to set email alerts
|

Josephson penetration depth in coplanar junctions based on 2D materials

Abstract: Josephson junctions and SQUIDs with graphene or other 2D materials as the weak link between superconductors have become a hot topic of research in recent years, with respect to both fundamental physics and potential applications. We have previously reported ultra-wide Josephson junctions (up to 80 μm wide) based on CVD graphene where the critical current was found to be uniformly distributed in the direction perpendicular to the current. In this paper, we demonstrate that the unusually large Josephson penetrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The developed equation in methodology section EQUATION ( 14) and EQUATION ( 9) and to study the nature of developed equation was computed using MATLAB and for this data form [26][27][28] and study the nature of JPD with temperature and with fermi velocity as shown in FIGURE 1 and 2 respectively. The nature of Josephson penetration Depth (JPD) to electronphonon and transition temperature in FIGURE 1 shoes that JPD decrease with increasing temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The developed equation in methodology section EQUATION ( 14) and EQUATION ( 9) and to study the nature of developed equation was computed using MATLAB and for this data form [26][27][28] and study the nature of JPD with temperature and with fermi velocity as shown in FIGURE 1 and 2 respectively. The nature of Josephson penetration Depth (JPD) to electronphonon and transition temperature in FIGURE 1 shoes that JPD decrease with increasing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has focused on Josephson junctions and superconducting quantum interference devices (SQUIDs) utilizing graphene or other 2D materials as weak links, with applications in both fundamental physics and potential technologies [26]. Ultrawide Josephson junctions based on chemical-vapor-deposition graphene have shown uniform critical current distribution.…”
Section: Perturbed Sine-gordon Equationmentioning
confidence: 99%